Understanding Zhongyong Using a Zhongyong Approach: Re-examining the Non-linear Relationship Between Creativity and the Confucian Doctrine of the Mean - Gao, Ruixiang; Huang, Shiqi; Yao, Yujie; Liu, Xiaoqin; Zhou, Yujun; Zhang, Shijia; Cai, Shaohua; Zuo, Huang; Zhan, Zehui; Mo, Lei (Frontiers in Psychology, 2022)
Zhongyong, a central theme of Confucian thought, refers to the “doctrine of the mean,” or the idea that moderation in all things is the optimal path. Despite considerable interest in the relationship between zhongyong and creativity, especially in China, studies of this relationship have not yielded consistent results. Based on a review of the literature, we hypothesized that this inconsistency arises from the dual nature of zhongyong itself, which has both a positive side, promoting creativity, and a negative side, inhibiting creativity. We also hypothesized that the negative side of zhongyong takes the form of excessive zhongyong. Indeed, the observations that every coin has two sides and that too much of a good thing is as bad as too little are core principles of zhongyong in traditional Chinese culture. To test these hypotheses, we conducted two empirical studies (measuring explicit and implicit zhongyong personality, respectively) to examine the relationships between positive and negative zhongyong and creativity (measured in terms of creative personality, divergent thinking, and convergent thinking). The results of both studies revealed an interaction between positive zhongyong and negative zhongyong, indicating that only a moderate level of zhongyong is conducive to creativity; both deficiency and excess are harmful. We discuss the implications of these results, suggesting that a zhongyong approach can help to clarify non-linear relationships between things, and recommending to re-assess the creativity of Chinese culture from a neutral and objective outlook. This paper deepens understanding of zhongyong and offers clear insights into creativity from an in-depth cultural perspective.